Analysis of Managerial Competence of School Principals in Improving the Performance of Elementary School Teachers in Banda Aceh City - Mujriyanti, Ana; Syarfuni, Syarfuni; Mardhatillah, Mardhatillah (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
Management ability is an ability that must be possessed by the principal in using school administrative management activities, including planning ability, organizational ability, implementation ability, and evaluation ability. The research aims to explore the managerial head in improving teacher performance. This research uses a type of qualitative research using descriptive. The instruments in the study are questionnaires, interviews, and observations. Data collection techniques use interview methods or interviews to parties who directly have relationships or interested parties in this study. This research uses a qualitative approach with a descriptive method, data collection in the research is carried out through interview guidelines. The subjects of the study were principals, supervisors and teachers at elementary schools under the Bungong Jeumpa Cluster of Banda Aceh City. The results of the study found that the school management process, it is seen that the quality of education in elementary schools has improved, and the principal has demonstrated various effective leadership qualities, including strong personality, decision-making ability and excellent communication skills, wholehearted dedication. etc. Acting as a school leader; encourage teachers to consistently carry out their duties and functions in accordance with the subjects they teach; implement leadership models that support the achievement of school goals.